Molecular characterization of two candidate genes associated with coat color in Tibetan sheep (Ovis arise) - Ji-long HAN; Min YANG; Ting-ting GUO; Yao-jing YUE; Jian-bin LIU; Chun-e NIU; Chao-feng WANG; Bo-hui YANG (Journal of Integrative Agriculture)
Coat color is a key economic trait in sheep. Some candidate genes associated with animal's coat color were found. Particularly, v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) and microphthalmia-associated transcription factor (MITF) play a key role in the modulation of hair pigmentation in mammals. This study investigated those two candidate genes' mutations and expressions associated with wool color in Tibetan sheep. First, the gene polymorphisms of those two genes were analyzed, and then, relative mRNA expression levels of those two genes in skin tissue with different coat colors were compared. Thirdly, KIT and MITF protein expression levels were detected through Western blot and immune-histochemical. Allele C was predominant allele in the white coat color Tibetan sheep population of the MITF coding region g. 1548 C/T loci. The relative MITF mRNA expression in black coat skin tissue was significantly higher than white (P<0.01). However, no significant differences were detected in the KIT gene's mRNA expression of these two different coat color skin tissues (P>0.05), while the level of KIT protein expression in skin tissues of white and black coats was also roughly equivalent. Our study observed that, the level of MITF protein expression in black coat skin tissue was significantly higher than that in white coat skin tissue, and positive staining for MITF protein expression was detected mainly in the epidermis and the dermal papilla, bulb, and outer root sheath of hair follicles. We conclude that the black coat of Tibetan sheep is related to high MITF expression in the hair follicles, and MITF may be important for coat color formation of Tibetan sheep.